ISOLASI DAN UJI AKTIVITAS ANTIBAKTERI MINYAK ATSIRI DARI RIMPANG LENGKUAS (Alpinia galanga L.) - Oka Adi Parwata, I M.; Sastra Dewi, P. Fanny (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and antibacterial activity test of the languas rhizomes (Alpinia galanga L.) essential oil was carried out The extract was yellow in colour with a volume of 3,5 mL. The activity test on E. coli bacteria at concentrations 100 ppm and 1000 ppm showed a retardation area of 7 mm and 9 mm in diameters. At 1000 ppm it retarded S. aureus bacteria to a diameter of 7 mm. Gas Chromatography – Mass Spectrometer data show that the essential oil of the languas rhizomes contains mainly 8 components : Dlimonen; Eukaliptol; 3-sikloheksen-1-ol, 4-metil-1-(1-metietil); Fenol, 4-(2-profenil)-asetat; 2,6-oktadien-1-ol, 3,7- dimetil-asetat; 1,6,10-dodekatrien, 7,11-dimetil-3-metilen; Pentadesen; sikloheksen, 1-metil-4-(5-metil-1-metilen-4- heksenil.
Keywords: antibacterial, essential oil, Alpinia galanga L.